KETERSEDIAAN RUANG TERBUKA HIJAU (RTH) DI KECAMATAN NANGGALO KOTA PADANG TAHUN 2022 - Claudia, Tiara; Iskarni, Paus (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
This study aims to know the availability of Green Open Space in Nanggalo Sub-district in 2022 and the suitability of the available Green Open Space to the Regional Spatial Plan (RTRW) of Padang City. The method used in this research is quantitative method with spatial approach. This research area is Nanggalo Sub-district and all its villages. The analysis technique used is overlay. The result of this research shows the availability of Green Open Space in Nanggalo Sub-district consists of two types of Green Open Space. The availability of Green Open Space in Nanggalo Sub-district for public use is available 20.67% while green open space for private use has not reached 10% which is only 8.15%, it can be concluded that in Nanggalo Sub-district the availability of public green open space is sufficient and private green open space is not sufficient.